Pengembangan Kompetensi Profesional Guru Pendidikan Agama Islam di SMK Tamtama 2 Prembun Kebumen - Echa Asmawati; Bahrun Ali Murtopo; Maesaroh Maesaroh (Tarbi: Jurnal Ilmiah Mahasiswa, 2023)
The purpose of this study was to determine the professional competence development of PAI teachers at SMK Tamtama 2 Prembun, to find out how to overcome the professional competence development of PAI teachers at SMK Tamtama 2 Prembun, and to know the factors supporting and inhibiting the development of professional competence of PAI teachers at SMK Tamtama 2 Prembun. This type of research is a qualitative research with a field research design which was carried out at SMK Tamtama 2 Prembun. The research subjects were the Principal, Deputy Head of Curriculum, PAI Teachers, and students. Data collection techniques using observation, interviews, and documentation. The components of data analysis used are data reduction, data presentation, and drawing conclusions. Based on the results of research on the development of professional competence of PAI teachers at SMK Tamtama 2 Prembun that they already have the ability, understanding and development of professional competencies according to their fields. PAI teachers' efforts in developing teacher professional competencies are by learning to be professional and conducting training, training, discussions with professional colleagues, seminars such as participating in MGMP activities in their respective schools. The supporting factors and inhibiting factors for the professional competence of PAI teachers are one of the facilities and infrastructure that support learning activities while the inhibiting factors such as PAI teachers have not been able to operate the learning media as a whole.